2021
DOI: 10.1007/s40122-021-00264-x
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Evidence for Control of Chronic Migraine Patients Receiving CGRP Monoclonal Antibody Therapy Added to OnabotulinumtoxinA: A Retrospective Chart Review

Abstract: Introduction Combination use of onabotulinumtoxinA and calcitonin gene–related peptide (CGRP) monoclonal antibodies (mAbs) has the potential to be more effective than either therapy alone for migraine prevention. Methods This retrospective, longitudinal chart review included adults with chronic migraine treated at one clinical site with ≥ 2 consecutive cycles of onabotulinumtoxinA and ≥ 1 month of subsequent combination treatment with CGRP mAbs. Charts at time of mAb pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 43 publications
0
41
0
2
Order By: Relevance
“…These findings are consistent with the results of other realworld studies evaluating the safety and efficacy of combination treatment with onabotulinumtoxinA and a CGRP mAb. The recent publication of a similar study by Blumenfeld et al (36) showed a 3.5-4 day reduction in MHD over 6-12 months of combination treatment after an initial mean reduction from 21.5 MHD to 12.1 MHD with onabotulinumtoxinA alone. A retrospective analysis by Armanious et al (33) recently demonstrated a 6.8-8.1 reduction in MHD in patients with CM who received 1-3 months of combination treatment with erenumab and onabotulinumtoxinA.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…These findings are consistent with the results of other realworld studies evaluating the safety and efficacy of combination treatment with onabotulinumtoxinA and a CGRP mAb. The recent publication of a similar study by Blumenfeld et al (36) showed a 3.5-4 day reduction in MHD over 6-12 months of combination treatment after an initial mean reduction from 21.5 MHD to 12.1 MHD with onabotulinumtoxinA alone. A retrospective analysis by Armanious et al (33) recently demonstrated a 6.8-8.1 reduction in MHD in patients with CM who received 1-3 months of combination treatment with erenumab and onabotulinumtoxinA.…”
Section: Discussionmentioning
confidence: 86%
“…The safety profile of combination treatment in this real-world study is consistent with that observed in prior analyses of each treatment alone and other real-world studies of CGRP mAbs added to onabotulinumtoxinA treatment for CM. In a similar study of combination preventive treatment of CM with onabotulinumtoxinA and a CGRP mAb by Blumenfeld et al ( 36 ) 28% of patients experienced an AE; the only one reported by ≥5% of patients was constipation. Another retrospective chart review of patients prescribed a CGRP mAb while receiving onabotulinumtoxinA for CM by Cohen et al ( 34 ) reported that AEs occurred in 8.5% of patients and included constipation, injection site reaction, and/or fatigue.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…On a smaller subset study population (n = 66) with quantifiable MHD data, patients receiving combined therapy have decreased 5.7 MHDs from onabot alone ( p < 0.001) and a total decrease of 16.6 MHDs (64.5% reduction from baseline, p < 0.001). Blumenfeld et al assessed 257 patients receiving concurrent onabot and CGRP-mAb therapy, reporting a MHD decrease of 3.5–4.0 [ 139 ]. Additionally, patients reported a mean decrease in Migraine Disability Assessment (MIDAS) scores of 6.1–11.1 points.…”
Section: Expert Opinion For Use In Migraine Treatmentmentioning
confidence: 99%